Method for improving damage of high-dose gallic acid to meat protein emulsification characteristic by using zein / polysaccharide nano system
By encapsulating gallic acid using zein/polysaccharide nanosystem, the problem of high-dose gallic acid damaging the emulsification performance of myofibrillary protein is solved, and the quality of emulsified meat products is improved and the antioxidant activity is maintained.
Patent Information
- Application Number
- CN202411774331.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-14
AI Technical Summary
High doses of gallic acid will damage the emulsification performance of myofibrillar protein in meat processing, resulting in a decrease in the quality of emulsified meat products.
Galic acid is encapsulated by zein/polysaccharide nanosystem, which increases the electrostatic and spatial repulsion between particles and inhibits the excessive modification of myofibrillary protein by polyphenols under oxidative stress, thereby improving the emulsification characteristics of meat proteins.
It effectively delays the flocculation/aggregation of oil droplets, improves the stability of the emulsion, improves the quality of emulsified meat products, and maintains the antioxidant activity of gallic acid.
Smart Images

Figure CN119605907A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of meat processing, and particularly relates to a method for improving the damage of high-dose gallic acid to the emulsification property of meat protein by utilizing a zein / polysaccharide nanosystem. Background Art
[0002] Myofibrillar protein accounts for about 55% of the total muscle protein in animals, and its emulsifying property determines the processing characteristics and edible quality of emulsified meat products. During meat processing and storage, myofibrillar protein is susceptible to free radical attack and excessive oxidation. Phytogenic phenolic compounds have attracted more and more attention due to their safe sources, good antioxidant capacity and pharmacological activity. In order to achieve an antioxidant effect equivalent to that of synthetic antioxidants, high doses of phenolic antioxidants are usually required in meat processing. However, high doses of phenolic compounds can induce excessive unfolding of the myofibrillar protein structure through covalent and / or non-covalent interactions, causing the protein to aggregate and precipitate under the action of strong hydrophobic forces, thereby shielding the hydrophobic groups, resulting in a reduction in the number of proteins adsorbed at the oil-water interface, which in turn impairs the emulsifying properties of myofibrillar protein.
[0003] Gallic acid (3,4,5-trihydroxybenzoic acid) is a natural, highly effective and readily available phenolic antioxidant. However, adding high doses of gallic acid to emulsified meat products has encountered difficulties and challenges. How to control the adverse interactions between natural polyphenols such as gallic acid and myofibrillar protein and improve the damage of high doses of phenolic antioxidants to the emulsification properties of myofibrillar protein is an urgent problem to be solved.
[0004] Zein contains more than 50% non-polar amino acids. The increase in solvent polarity will lead to a decrease in protein solubility and a change in protein conformation, which is beneficial to the self-assembly of zein. This makes zein nanoparticles an ideal carrier for encapsulating bioactive substances. However, zein nanoparticles are unstable and prone to aggregation. The use of anionic hydrophilic polysaccharides as charged coatings has been shown to improve the stability of zein nanoparticles by increasing the electrostatic and spatial repulsion between particles. Based on the above background, the present invention utilizes a zein / polysaccharide nanosystem to encapsulate gallic acid, and without affecting the antioxidant activity of gallic acid, inhibits the excessive modification of myofibrillar proteins by polyphenols under oxidative stress, thereby improving the emulsification properties of meat protein and improving the quality of emulsified meat products. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a method for improving the damage of high-dose gallic acid to the emulsifying properties of meat protein by using a zein / polysaccharide nanosystem, so as to improve the emulsifying properties of myofibrillar protein and improve the quality of emulsified meat products.
[0006] The technical solution adopted to achieve the purpose of the present invention is:
[0007] A method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, comprising the following steps:
[0008] Step 1, extracting myofibrillar protein from chicken breast;
[0009] Step 2, adding the myofibrillar protein obtained in step 1 to the gallic acid-zein / polysaccharide nanocomposite solution, and homogenizing with a homogenizer to obtain a myofibrillar protein suspension;
[0010] Step 3, adding the Fenton oxidation system to the myofibrillar protein suspension obtained in step 2 to obtain a myofibrillar protein sample; reacting the myofibrillar protein sample in an environment of 0 to 4° C. for 10 to 14 hours to obtain a reacted myofibrillar protein sample;
[0011] Step 4: Mix the myofibrillar protein sample obtained in step 3 with soybean oil, and homogenize with a homogenizer to obtain an oil-in-water emulsion, which is a myofibrillar protein-based emulsion with improved emulsification properties.
[0012] Further, in step 2, the gallic acid-zein / polysaccharide nanocomposite solution preparation process is as follows:
[0013] Step 21, dissolving 15 to 30 mg of zein in 8 to 12 mL of an ethanol aqueous solution having a volume fraction of 80% to 95%, and stirring with a magnetic stirrer for 0.5 to 2 h to obtain a zein solution;
[0014] Step 22, adding 2 mg of gallic acid to the zein solution obtained in step 21, stirring with a magnetic stirrer for 1.5 to 3 hours to obtain a gallic acid-zein mixture; then centrifuging the gallic acid-zein mixture at a speed of 2000 to 5000 g for 10 minutes using a centrifuge, and the obtained supernatant is the gallic acid-zein solution;
[0015] Step 23, dissolving 30-45 mg of polysaccharide in 18-22 mL of deionized water, stirring with a magnetic stirrer for 0.5-2 h to obtain a polysaccharide aqueous solution; adjusting the pH value of the polysaccharide aqueous solution to 3.5-5.0 with a 1 mol / L hydrochloric acid solution to obtain a polysaccharide solution;
[0016] Step 24, under magnetic stirring conditions, dropwise adding the gallic acid-zein solution obtained in step 22 into 8-12 mL of deionized water with a pH value of 3.5-5.0, and continuing to stir with a magnetic stirrer for 3-8 minutes to obtain a gallic acid-zein ethanol dispersion; removing ethanol from the gallic acid-zein ethanol dispersion by a rotary evaporator, and then adding deionized water with a pH value of 3.5-5.0 to supplement the total volume to 18-22 mL, to obtain a gallic acid-zein dispersion;
[0017] Step 25. Under magnetic stirring conditions, add the gallic acid-zein dispersion obtained in step 24 to the polysaccharide solution obtained in step 23, and continue stirring with a magnetic stirrer for 3 to 8 minutes to obtain a gallic acid-zein / polysaccharide complex; centrifuge the gallic acid-zein / polysaccharide complex at a speed of 2000 to 5000 g for 10 minutes to obtain a supernatant, and then dry the supernatant with a freeze dryer to obtain a gallic acid-zein / polysaccharide nanocomposite powder.
[0018] Step 26: dissolving the gallic acid-zein / polysaccharide nanocomposite powder obtained in step 25 in 14-18 mL of a 0.6 mol / L sodium chloride solution to obtain a gallic acid-zein / polysaccharide nanocomposite solution.
[0019] Furthermore, in step 23, the polysaccharide is sodium alginate, gum arabic or xanthan gum.
[0020] Further, in step 3, the final concentration of myofibrillar protein in the myofibrillar protein sample is 4-8 mg / mL, the final concentration of ferric chloride in the Fenton oxidation system is 25-40 μmol / L, the final concentration of ascorbic acid is 275-350 μmol / L, and the final concentration of hydrogen peroxide is 8-12 mmol / L.
[0021] Furthermore, in step 4, the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:1.
[0022] Furthermore, in step 4, the speed of the homogenization process is 10000-13000 rpm, and the homogenization time is 1-3 min.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The present invention provides a method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem. The use of zein / polysaccharide nanoparticles to encapsulate gallic acid effectively inhibits the covalent and non-covalent interactions between gallic acid and myofibrillar protein under oxidative stress, and reduces the excessive aggregation of myofibrillar protein induced by high-dose gallic acid. This promotes the diffusion of myofibrillar protein to the oil-water interface, resulting in a decrease in interfacial tension and a smaller droplet size, thereby delaying the flocculation / agglomeration of oil droplets and improving the stability of the emulsion. In addition, the presence of anionic polysaccharides increases the viscosity of the continuous phase and the electrostatic repulsion of the emulsion system, making the oil droplets more evenly distributed and the physical stability better. Therefore, the myofibrillar protein-based emulsion with improved emulsification properties has a higher emulsification activity and a lower creaming index, thereby effectively improving the quality of emulsified meat products.
[0025] 2. The preparation method of the gallic acid-zein / polysaccharide nanocomplex provided by the present invention is simple and has strong practicality. Zein is a food-derived protein widely present in plants, is inexpensive, has good self-assembly, and has broad application prospects in the embedding and delivery of bioactive substances and drugs. In addition, zein can also be degraded into bioactive peptides that are beneficial to human health and have good biocompatibility. The anionic polysaccharides used in the present invention are all natural hydrophilic colloids, widely available, green and edible. Using anionic hydrophilic polysaccharides as charged coatings can improve the stability of zein nanoparticles and have a higher encapsulation rate for phenolic substances.
[0026] 3. The present invention provides a method for increasing the amount of phenolic antioxidants added without destroying the functional properties of meat protein. Replacing artificial synthetic antioxidants with high doses of natural phenolic antioxidants meets the development needs of safe and healthy food. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The three-phase contact angle measurement results of myofibrillar protein particles in Comparative Examples 1-3 and Examples 1-3;
[0028] Figure 2 The interfacial tension measurement results of myofibrillar proteins in Comparative Examples 1-3 and Examples 1-3;
[0029] Figure 3 The zeta potential measurement results of the myofibrillar protein-based emulsions in Comparative Examples 1-3 and Examples 1-3;
[0030] Figure 4 The particle size distribution measurement results of the myofibrillar protein-based emulsions in Comparative Examples 1-3 and Examples 1-3;
[0031] Figure 5is the average particle size D of the myofibrillar protein-based emulsion in Comparative Examples 1-3 and Examples 1-3 4,3 Measurement results;
[0032] Figure 6 It is a confocal laser scanning microscope (CLSM) microstructure diagram of the myofibrillar protein-based emulsion in Comparative Examples 1-3 and Examples 1-3;
[0033] Figure 7 The emulsion behavior photos of the myofibrillar protein-based emulsions in Comparative Examples 1-3 and Examples 1-3;
[0034] Figure 8 The turbiscan stability index (TSI) test results of the myofibrillar protein-based emulsions in Comparative Examples 1-3 and Examples 1-3;
[0035] Fig. 9 The backscattered light intensity (ΔBS) of the myofibrillar protein-based emulsions in Comparative Examples 1-3 and Examples 1-3 is measured;
[0036] Fig.10 The microrheological properties of the myofibrillar protein-based emulsions in Comparative Examples 1-3 and Examples 1-3 are as follows: (A) macroscopic viscosity index (MVI); (B) fluidity index (FI); (C) elasticity index (EI);
[0037] Fig.11 The average particle size measurement results of gallic acid-zein / sodium alginate (GA-zein / SA), gallic acid-zein / gum arabic (GA-zein / AG), and gallic acid-zein / xanthan gum (GA-zein / XG) nanocomposites;
[0038] Fig.12 These are the results of zeta potential measurements of gallic acid, zein, gallic acid-zein / sodium alginate (GA-zein / SA), gallic acid-zein / gum arabic (GA-zein / AG), and gallic acid-zein / xanthan gum (GA-zein / XG) nanocomposites. DETAILED DESCRIPTION
[0039] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described below are only used to explain the present invention and are not used to limit the present invention.
[0040] The present invention provides a method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using a zein / polysaccharide nanosystem, comprising the following steps:
[0041] Step 1, extracting myofibrillar protein from chicken breast; the extraction process specifically includes the following steps:
[0042] Step 11, chop fresh chicken breast with a knife, add it to the protein treatment solution to obtain a mixture; homogenize the mixture and centrifuge to obtain a precipitate; add the protein treatment solution to the precipitate and repeat the above homogenization and centrifugation operations 1 to 2 times to obtain crude protein particles. Wherein, the concentration of NaCl in the protein treatment solution is 0.08 to 0.12 mol / L, the concentration of MgCl2 is 0.001 to 0.003 mol / L, the concentration of EDTA-2Na is 0.0008 to 0.0012 mol / L, the concentration of NaH2PO4 / Na2HPO4 buffer is 0.08 to 0.12 mol / L, and the pH is 6.95 to 7.05; the mass volume ratio (w / v) of chicken breast to protein treatment solution is 1:3 to 1:5; the homogenization conditions are 20s×3 times, the rotation speed is 12000 to 14000 rpm; the centrifugation conditions are 0 to 4°C, the rotation speed is 4000 to 5500g, and the time is 15min.
[0043] Step 12, adding the crude protein particles obtained in step 11 to a NaCl solution with a concentration of 0.08-0.12 mol / L, homogenizing, centrifuging, and obtaining a precipitate; adding the NaCl solution to the precipitate, repeating the above homogenization and centrifugation operations 1-2 times to obtain the final precipitate, which is myofibrillar protein. The mass volume ratio (w / v) of the crude protein particles to the NaCl solution is 1:3-1:5; the homogenization conditions and centrifugation conditions are the same as those in step 11.
[0044] Step 13: Using bovine serum albumin as a standard protein, the protein content of the myofibrillar protein obtained in step 12 is determined by the biuret method.
[0045] Step 2, preparation of gallic acid-zein / polysaccharide nanocomposite solution and addition of myofibrillar protein, specifically comprises the following steps:
[0046] Step 21, dissolving 15 to 30 mg of zein in 8 to 12 mL of an ethanol aqueous solution having a volume fraction of 80% to 95%, and stirring with a magnetic stirrer for 0.5 to 2 h to obtain a zein solution;
[0047] Step 22, adding 2 mg of gallic acid to the zein solution obtained in step 21, stirring with a magnetic stirrer for 1.5 to 3 hours to obtain a gallic acid-zein mixture; then centrifuging the gallic acid-zein mixture at a speed of 2000 to 5000 g for 10 minutes using a centrifuge, and the obtained supernatant is the gallic acid-zein solution;
[0048] Step 23, dissolving 30-45 mg of polysaccharide in 18-22 mL of deionized water, stirring with a magnetic stirrer for 0.5-2 h to obtain a polysaccharide aqueous solution; adjusting the pH value of the polysaccharide aqueous solution to 3.5-5.0 with a 1 mol / L hydrochloric acid solution to obtain a polysaccharide solution; wherein the polysaccharide is sodium alginate, gum arabic or xanthan gum;
[0049] Step 24, under magnetic stirring conditions, dropwise adding the gallic acid-zein solution obtained in step 22 into 8-12 mL of deionized water with a pH value of 3.5-5.0, and continuing to stir with a magnetic stirrer for 3-8 minutes to obtain a gallic acid-zein ethanol dispersion; removing ethanol from the gallic acid-zein ethanol dispersion by a rotary evaporator, and then adding deionized water with a pH value of 3.5-5.0 to supplement the total volume to 18-22 mL, to obtain a gallic acid-zein dispersion;
[0050] Step 25. Under magnetic stirring conditions, add the gallic acid-zein dispersion obtained in step 24 to the polysaccharide solution obtained in step 23, and continue stirring with a magnetic stirrer for 3 to 8 minutes to obtain a gallic acid-zein / polysaccharide complex; centrifuge the gallic acid-zein / polysaccharide complex at a speed of 2000 to 5000 g for 10 minutes to obtain a supernatant, and then dry the supernatant with a freeze dryer to obtain a gallic acid-zein / polysaccharide nanocomposite powder.
[0051] Step 26: dissolving the gallic acid-zein / polysaccharide nanocomposite powder obtained in step 25 in 14-18 mL of a 0.6 mol / L sodium chloride solution to obtain a gallic acid-zein / polysaccharide nanocomposite solution.
[0052] Step 27: adding the myofibrillar protein obtained in step 12 to the gallic acid-zein / polysaccharide nanocomposite solution obtained in step 26, and homogenizing with a homogenizer to obtain a myofibrillar protein suspension.
[0053] Step 3: Addition of oxidation system, the specific process is as follows:
[0054] Add the Fenton oxidation system to the myofibrillar protein suspension obtained in step 27 to obtain a myofibrillar protein sample; react the myofibrillar protein sample in an environment of 0 to 4° C. for 10 to 14 hours to obtain a reacted myofibrillar protein sample; wherein the final concentration of myofibrillar protein in the myofibrillar protein sample is 4 to 8 mg / mL, the final concentration of ferric chloride in the Fenton oxidation system is 25 to 40 μmol / L, the final concentration of ascorbic acid is 275 to 350 μmol / L, and the final concentration of hydrogen peroxide is 8 to 12 mmol / L.
[0055] Step 4, preparation of myofibrillar protein-based emulsion, the specific process is as follows:
[0056] The myofibrillar protein sample after the reaction obtained in step 3 is mixed with soybean oil, and homogenized with a homogenizer to obtain an oil-in-water emulsion, which is a myofibrillar protein-based emulsion with improved emulsification properties; wherein the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:1; the rotation speed of the homogenization process is 10000 to 13000 rpm, and the homogenization time is 1 to 3 minutes.
[0057] Step 5: Determine the emulsification activity and creaming index of the myofibrillar protein-based emulsion obtained in step 4. The specific process is as follows:
[0058] Determination of emulsification activity: Take the myofibrillar protein-based emulsion and place it in a cylindrical glass bottle. Carefully draw 300 μL of the emulsion at 1 mm from the bottom of the bottle and mix it with 10 mL of 0.1% (w / v) sodium dodecyl sulfate solution (SDS). Using 0.1% SDS as a control, measure the absorbance value at a wavelength of 500 nm. The emulsification activity index (EAI) is calculated according to formula 1:
[0059]
[0060] Where A0 is the absorbance value, n is the dilution factor of the emulsion, C is the protein concentration (g / mL), is the volume fraction of soybean oil.
[0061] Determination of creaming index: Take the myofibrillar protein-based emulsion and place it in a graduated glass tube and store it at room temperature for 1 hour. The creaming index (CI) is calculated according to formula 2:
[0062]
[0063] Where H1 is the height of the bottom clear liquid, and H0 is the initial total height of the emulsion.
[0064] Comparative Example 1
[0065] A method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, comprising the following steps:
[0066] Step 1, extracting myofibrillar protein from chicken breast;
[0067] Step 11, chop fresh chicken breast with a knife, add it to the protein treatment solution to obtain a mixture; homogenize the mixture and centrifuge to obtain a precipitate; add the protein treatment solution to the precipitate and repeat the above homogenization and centrifugation operations 1 to 2 times to obtain crude protein particles. Wherein, the concentration of NaCl in the protein treatment solution is 0.08 to 0.12 mol / L, the concentration of MgCl2 is 0.001 to 0.003 mol / L, the concentration of EDTA-2Na is 0.0008 to 0.0012 mol / L, the concentration of NaH2PO4 / Na2HPO4 buffer is 0.08 to 0.12 mol / L, and the pH is 6.95 to 7.05; the mass volume ratio (w / v) of chicken breast to protein treatment solution is 1:3 to 1:5: the homogenization conditions are 20s×3 times, the rotation speed is 12000 to 14000 rpm; the centrifugation conditions are 0 to 4°C, the rotation speed is 4000 to 5500g, and the time is 15min.
[0068] Step 12, adding the crude protein particles obtained in step 11 to a NaCl solution with a concentration of 0.08-0.12 mol / L, homogenizing, centrifuging, and obtaining a precipitate; adding the NaCl solution to the precipitate, repeating the above homogenization and centrifugation operations 1-2 times to obtain the final precipitate, which is myofibrillar protein. The mass volume ratio (w / v) of the crude protein particles to the NaCl solution is 1:3-1:5; the homogenization conditions and centrifugation conditions are the same as those in step 11.
[0069] Step 13: Using bovine serum albumin as a standard protein, the protein content of the myofibrillar protein obtained in step 12 is determined by the biuret method.
[0070] Step 2, myofibrillar protein blank control treatment, the specific process is as follows:
[0071] The myofibrillar protein obtained in step 12 is added to 14-18 mL of a sodium chloride solution with a concentration of 0.6 mol / L, and homogenized with a homogenizer to obtain a myofibrillar protein suspension; the myofibrillar protein suspension is reacted in an environment of 0-4° C. for 10-14 hours to obtain a myofibrillar protein sample after the reaction; wherein the final concentration of the myofibrillar protein in the myofibrillar protein suspension is 4-8 mg / mL.
[0072] Step 3, preparation of myofibrillar protein-based emulsion, the specific process is as follows:
[0073] The myofibrillar protein sample after the reaction obtained in step 2 is mixed with soybean oil, and homogenized with a homogenizer to obtain an oil-in-water emulsion, which is the myofibrillar protein-based emulsion of the blank control group; wherein the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:1; the rotation speed of the homogenization process is 10000 to 13000 rpm, and the homogenization time is 1 to 3 min.
[0074] The emulsification activity and emulsion index of the myofibrillar protein-based emulsion in the blank control group obtained in this comparative example were measured. The emulsification activity of the myofibrillar protein-based emulsion in the blank control group was 4.91 m / s. 2 / g, and the creaming index is 0%.
[0075] Comparative Example 2
[0076] A method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, comprising the following steps:
[0077] Step 1, extracting myofibrillar protein from chicken breast;
[0078] Step 11, chop fresh chicken breast with a knife, add it to the protein treatment solution to obtain a mixture; homogenize the mixture and centrifuge to obtain a precipitate; add the protein treatment solution to the precipitate and repeat the above homogenization and centrifugation operations 1 to 2 times to obtain crude protein particles. Wherein, the concentration of NaCl in the protein treatment solution is 0.08 to 0.12 mol / L, the concentration of MgCl2 is 0.001 to 0.003 mol / L, the concentration of EDTA-2Na is 0.0008 to 0.0012 mol / L, the concentration of NaH2PO4 / Na2HPO4 buffer is 0.08 to 0.12 mol / L, pH 6.95 to 7.05: the mass volume ratio (w / v) of chicken breast to protein treatment solution is 1:3 to 1:5; the homogenization conditions are 20s×3 times, the rotation speed is 12000 to 14000 rpm; the centrifugation conditions are 0 to 4°C, the rotation speed is 4000 to 5500g, and the time is 15min.
[0079] Step 12, adding the crude protein particles obtained in step 11 to a NaCl solution with a concentration of 0.08-0.12 mol / L, homogenizing, centrifuging, and obtaining a precipitate; adding the NaCl solution to the precipitate, repeating the above homogenization and centrifugation operations 1-2 times to obtain the final precipitate, which is myofibrillar protein. The mass volume ratio (w / v) of the crude protein particles to the NaCl solution is 1:3-1:5; the homogenization conditions and centrifugation conditions are the same as those in step 11.
[0080] Step 13: Using bovine serum albumin as a standard protein, the protein content of the myofibrillar protein obtained in step 12 is determined by the biuret method.
[0081] Step 2, myofibrillar protein oxidation control treatment, the specific process is as follows:
[0082] The myofibrillar protein obtained in step 12 is added to 14-18 mL of a sodium chloride solution with a concentration of 0.6 mol / L, and homogenized with a homogenizer to obtain a myofibrillar protein suspension; a Fenton oxidation system is added to the myofibrillar protein suspension to obtain a myofibrillar protein sample; the myofibrillar protein sample is reacted in an environment of 0-4° C. for 10-14 hours to obtain a myofibrillar protein sample after reaction; wherein the final concentration of myofibrillar protein in the myofibrillar protein sample is 4-8 mg / mL, the final concentration of ferric chloride in the Fenton oxidation system is 25-40 μmol / L, the final concentration of ascorbic acid is 275-350 μmol / L, and the final concentration of hydrogen peroxide is 8-12 mmol / L.
[0083] Step 3, preparation of myofibrillar protein-based emulsion, the specific process is as follows:
[0084] The myofibrillar protein sample after the reaction obtained in step 2 is mixed with soybean oil, and homogenized with a homogenizer to obtain an oil-in-water emulsion, which is the myofibrillar protein-based emulsion of the oxidation control group; wherein the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:1; the rotation speed of the homogenization process is 10000 to 13000 rpm, and the homogenization time is 1 to 3 min.
[0085] The emulsification activity and emulsion index of the myofibrillar protein-based emulsion in the oxidized control group obtained in this comparative example were measured. The emulsification activity of the myofibrillar protein-based emulsion in the oxidized control group was 5.49 m / s. 2 / g, and the creaming index is 0%. Compared with Comparative Example 1, the emulsifying activity of the myofibrillar protein-based emulsion in the oxidized control group obtained in this comparative example is increased by 11%.
[0086] Comparative Example 3
[0087] A method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, comprising the following steps:
[0088] Step 1, extracting myofibrillar protein from chicken breast;
[0089] Step 11, chop fresh chicken breast with a knife, add it to the protein treatment solution to obtain a mixture; homogenize the mixture and centrifuge to obtain a precipitate; add the protein treatment solution to the precipitate and repeat the above homogenization and centrifugation operations 1 to 2 times to obtain crude protein particles. Wherein, the concentration of NaCl in the protein treatment solution is 0.08 to 0.12 mol / L, the concentration of MgCl2 is 0.001 to 0.003 mol / L, the concentration of EDTA-2Na is 0.0008 to 0.0012 mol / L, the concentration of NaH2PO4 / Na2HPO4 buffer is 0.08 to 0.12 mol / L, pH 6.95 to 7.05: the mass volume ratio (w / v) of chicken breast to protein treatment solution is 1:3 to 1:5; the homogenization conditions are 20s×3 times, the rotation speed is 12000 to 14000 rpm; the centrifugation conditions are 0 to 4°C, the rotation speed is 4000 to 5500g, and the time is 15min.
[0090] Step 12, adding the crude protein particles obtained in step 11 to a NaCl solution with a concentration of 0.08-0.12 mol / L, homogenizing, centrifuging, and obtaining a precipitate; adding the NaCl solution to the precipitate, repeating the above homogenization and centrifugation operations 1-2 times to obtain the final precipitate, which is myofibrillar protein. The mass volume ratio (w / v) of the crude protein particles to the NaCl solution is 1:3-1:5; the homogenization conditions and centrifugation conditions are the same as those in step 11.
[0091] Step 13: Using bovine serum albumin as a standard protein, the protein content of the myofibrillar protein obtained in step 12 is determined by the biuret method.
[0092] Step 2: Preparation of high-dose gallic acid solution and addition of myofibrillar protein. The specific process is as follows:
[0093] Dissolve 2 mg of gallic acid in 14-18 mL of a 0.6 mol / L sodium chloride solution to obtain a gallic acid solution; add the myofibrillar protein obtained in step 12 to the gallic acid solution, and homogenize with a homogenizer to obtain a myofibrillar protein suspension.
[0094] Step 3: Addition of oxidation system, the specific process is as follows:
[0095] Add the Fenton oxidation system to the myofibrillar protein suspension obtained in step 2 to obtain a myofibrillar protein sample; react the myofibrillar protein sample in an environment of 0 to 4° C. for 10 to 14 hours to obtain a reacted myofibrillar protein sample; wherein the final concentration of myofibrillar protein in the myofibrillar protein sample is 4 to 8 mg / mL, the final concentration of ferric chloride in the Fenton oxidation system is 25 to 40 μmol / L, the final concentration of ascorbic acid is 275 to 350 μmol / L, and the final concentration of hydrogen peroxide is 8 to 12 mmol / L.
[0096] Step 4, preparation of myofibrillar protein-based emulsion, the specific process is as follows:
[0097] The myofibrillar protein sample after the reaction obtained in step 3 is mixed with soybean oil, and homogenized with a homogenizer to obtain an oil-in-water emulsion, which is a polyphenol-damaged myofibrillar protein-based emulsion; wherein the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:1; the rotation speed of the homogenization process is 10000 to 13000 rpm, and the homogenization time is 1 to 3 minutes.
[0098] The emulsification activity and emulsion index of the polyphenol-damaged myofibrillar protein-based emulsion obtained in this comparative example were measured. The emulsification activity of the polyphenol-damaged myofibrillar protein-based emulsion was 1.12 m 2 / g, and the creaming index is 3.38%. Compared with Comparative Example 2, the emulsifying activity of the polyphenol-damaged myofibrillar protein-based emulsion obtained in this comparative example decreased by 80%, and the creaming index increased from 0% to 3.38%.
[0099] Example 1
[0100] A method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, comprising the following steps:
[0101] Step 1, extracting myofibrillar protein from chicken breast;
[0102] Step 11, chop fresh chicken breast with a knife, add it to the protein treatment solution to obtain a mixture; homogenize the mixture and centrifuge to obtain a precipitate; add the protein treatment solution to the precipitate and repeat the above homogenization and centrifugation operations 1 to 2 times to obtain crude protein particles. Wherein, the concentration of NaCl in the protein treatment solution is 0.08 to 0.12 mol / L, the concentration of MgCl2 is 0.001 to 0.003 mol / L, the concentration of EDTA-2Na is 0.0008 to 0.0012 mol / L, the concentration of NaH2PO4 / Na2HPO4 buffer is 0.08 to 0.12 mol / L, and the pH is 6.95 to 7.05; the mass volume ratio (w / v) of chicken breast to protein treatment solution is 1:3 to 1:5; the homogenization conditions are 20s×3 times, the rotation speed is 12000 to 14000 rpm; the centrifugation conditions are 0 to 4°C, the rotation speed is 4000 to 5500g, and the time is 15min.
[0103] Step 12, adding the crude protein particles obtained in step 11 to a NaCl solution with a concentration of 0.08-0.12 mol / L, homogenizing, centrifuging, and obtaining a precipitate; adding the NaCl solution to the precipitate, repeating the above homogenization and centrifugation operations 1-2 times to obtain the final precipitate, which is myofibrillar protein. The mass volume ratio (w / v) of the crude protein particles to the NaCl solution is 1:3-1:5; the homogenization conditions and centrifugation conditions are the same as those in step 11.
[0104] Step 13: Using bovine serum albumin as a standard protein, the protein content of the myofibrillar protein obtained in step 12 is determined by the biuret method.
[0105] Step 2, preparation of gallic acid-zein / polysaccharide nanocomposite solution and addition of myofibrillar protein, specifically comprises the following steps:
[0106] Step 21, dissolving 15 to 30 mg of zein in 8 to 12 mL of an ethanol aqueous solution having a volume fraction of 80% to 95%, and stirring with a magnetic stirrer for 0.5 to 2 h to obtain a zein solution;
[0107] Step 22, adding 2 mg of gallic acid to the zein solution obtained in step 21, stirring with a magnetic stirrer for 1.5 to 3 hours to obtain a gallic acid-zein mixture; then centrifuging the gallic acid-zein mixture at a speed of 2000 to 5000 g for 10 minutes using a centrifuge, and the obtained supernatant is the gallic acid-zein solution;
[0108] Step 23, dissolving 30-45 mg of polysaccharide in 18-22 mL of deionized water, stirring with a magnetic stirrer for 0.5-2 h to obtain a polysaccharide aqueous solution; adjusting the pH value of the polysaccharide aqueous solution to 3.5-5.0 with a 1 mol / L hydrochloric acid solution to obtain a polysaccharide solution; wherein the polysaccharide is sodium alginate;
[0109] Step 24, under magnetic stirring conditions, dropwise adding the gallic acid-zein solution obtained in step 22 into 8-12 mL of deionized water with a pH value of 3.5-5.0, and continuing to stir with a magnetic stirrer for 3-8 minutes to obtain a gallic acid-zein ethanol dispersion; removing ethanol from the gallic acid-zein ethanol dispersion by a rotary evaporator, and then adding deionized water with a pH value of 3.5-5.0 to supplement the total volume to 18-22 mL, to obtain a gallic acid-zein dispersion;
[0110] Step 25. Under magnetic stirring conditions, add the gallic acid-zein dispersion obtained in step 24 to the polysaccharide solution obtained in step 23, and continue stirring with a magnetic stirrer for 3 to 8 minutes to obtain a gallic acid-zein / polysaccharide complex; centrifuge the gallic acid-zein / polysaccharide complex at a speed of 2000 to 5000 g for 10 minutes to obtain a supernatant, and then dry the supernatant with a freeze dryer to obtain a gallic acid-zein / polysaccharide nanocomposite powder.
[0111] Step 26: dissolving the gallic acid-zein / polysaccharide nanocomposite powder obtained in step 25 in 14-18 mL of a 0.6 mol / L sodium chloride solution to obtain a gallic acid-zein / polysaccharide nanocomposite solution.
[0112] Step 27: adding the myofibrillar protein obtained in step 12 to the gallic acid-zein / polysaccharide nanocomposite solution obtained in step 26, and homogenizing with a homogenizer to obtain a myofibrillar protein suspension.
[0113] Step 3: Addition of oxidation system, the specific process is as follows:
[0114] Add the Fenton oxidation system to the myofibrillar protein suspension obtained in step 27 to obtain a myofibrillar protein sample; react the myofibrillar protein sample in an environment of 0 to 4° C. for 10 to 14 hours to obtain a reacted myofibrillar protein sample; wherein the final concentration of myofibrillar protein in the myofibrillar protein sample is 4 to 8 mg / mL, the final concentration of ferric chloride in the Fenton oxidation system is 25 to 40 μmol / L, the final concentration of ascorbic acid is 275 to 350 μmol / L, and the final concentration of hydrogen peroxide is 8 to 12 mmol / L.
[0115] Step 4, preparation of myofibrillar protein-based emulsion, the specific process is as follows:
[0116] The myofibrillar protein sample after the reaction obtained in step 3 is mixed with soybean oil, and homogenized with a homogenizer to obtain an oil-in-water emulsion, which is a myofibrillar protein-based emulsion with improved emulsification properties; wherein the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:1; the rotation speed of the homogenization process is 10000 to 13000 rpm, and the homogenization time is 1 to 3 minutes.
[0117] The emulsification activity and emulsion index of the myosin-based emulsion with improved emulsification properties obtained in this example were measured. The emulsification activity of the myosin-based emulsion with improved emulsification properties was 5.73 m / s. 2 / g, and the creaming index is 0%. Compared with Comparative Example 3, the emulsifying activity of the myofibrillar protein-based emulsion with improved emulsifying properties obtained in this example is increased by 4.1 times, and the creaming index is reduced by 100%.
[0118] Example 2
[0119] This Example 2 provides a method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using a zein / polysaccharide nanosystem. The operation steps of this Example 2 are different from those of Example 1 in that: in step 23, the polysaccharide is gum arabic. The other operation steps of this Example 2 are the same as those of Example 1.
[0120] The emulsification activity and emulsion index of the myosin-based emulsion with improved emulsification properties obtained in this example were measured. The emulsification activity of the myosin-based emulsion with improved emulsification properties was 5.85 m / s. 2 / g, and the creaming index is 0.77%. Compared with Comparative Example 3, the emulsifying activity of the myofibrillar protein-based emulsion with improved emulsifying properties obtained in this example is increased by 4.2 times, and the creaming index is reduced by 77%.
[0121] Example 3
[0122] This Example 3 provides a method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using a zein / polysaccharide nanosystem. The operation steps of this Example 3 are different from those of Example 1 in that: in step 23, the polysaccharide is xanthan gum. The other operation steps of this Example 3 are the same as those of Example 1.
[0123] The emulsification activity and emulsion index of the myosin-based emulsion with improved emulsification properties obtained in this example were measured. The emulsification activity of the myosin-based emulsion with improved emulsification properties was 5.83 m / s. 2 / g, and the creaming index is 1.12%. Compared with Comparative Example 3, the emulsifying activity of the myofibrillar protein-based emulsion with improved emulsifying properties obtained in this example is increased by 4.2 times, and the creaming index is reduced by 67%.
[0124] The examples were compared with the comparative examples, and the results are shown in Table 1. Compared with the blank control group (Comparative Example 1), the emulsifying activity of the oxidized control group (Comparative Example 2) increased significantly (p<0.05), which is because oxidation causes the myofibrillar protein structure to unfold appropriately, and the exposed hydrophobic groups are conducive to the combination of protein and oil droplets. The emulsifying activity of the polyphenol-damaged group (Comparative Example 3) is only 1.12 m 2 / g, compared with the oxidized control group, the emulsifying activity decreased by 80%, and the creaming index increased from 0% to 3.38%, indicating that the emulsion stability decreased. This is because high doses of gallic acid covalently and non-covalently bind to myofibrillar protein, inducing protein aggregation and hindering the diffusion of protein to the oil-water interface layer, causing oil droplets to become unstable and coalesce. Compared with the polyphenol-damaged group, the emulsifying activity of myofibrillar protein-based emulsion with improved emulsifying properties increased by 4.1 to 4.2 times, and the creaming index decreased by 67% to 100%. The use of zein / polysaccharide nanosystem to encapsulate gallic acid hinders the excessive modification of myofibrillar protein by gallic acid, prompting more proteins to participate in the formation of the interfacial film, thereby improving the emulsifying activity and emulsion stability.
[0125] Table 1 Comparison of emulsifying activity and creaming index of myofibrillar protein-based emulsions obtained in Examples and Comparative Examples
[0126] <![CDATA[Emulsifying activity (m 2 / g)]]> Milking index (%) Comparative Example 1 (blank control group) <![CDATA[4.91±0.02 b ]]> 0 Comparative Example 2 (Oxidation Control Group) <![CDATA[5.49±0.04 c ]]> 0 Comparative Example 3 (polyphenol damage group) <![CDATA[1.12±0.04 a ]]> 3.38 Example 1 (Emulsification property improved group 1) <![CDATA[5.73±0.06 d ]]> 0 Example 2 (Emulsification property improved group 2) <![CDATA[5.85±0.05 e ]]> 0.77 Example 3 (Emulsification property improved group 3) <![CDATA[5.83±0.04 e ]]> 1.12
[0127]
Determination of emulsification properties of myofibrillar protein-based emulsion
[0128] 1. Experimental methods:
[0129] 1-1. Determination of wettability: Use KRUSS drop shape analyzer (model DSA100) to measure the three-phase contact angle to evaluate the wettability of the sample. The reacted myofibrillar protein sample was dried into powder using a freeze dryer. The powder was pressed into a circular sheet with a thickness of 2 mm and a diameter of 10 mm, and soaked in soybean oil for 5 minutes. Use a high-precision syringe to drop 5 μL of deionized water on the surface of the sheet, and use a camera to take an image of the contact surface after 30 seconds. The Young-Laplace equation was used to analyze the three-phase contact angle.
[0130] 1-2. Determination of surface tension: Use KRUSS drop shape analyzer (model DSA100) to dynamically monitor the interfacial tension between the water phase and the oil phase. Dilute the reacted myofibrillar protein sample to a concentration of 1 mg / mL with a sodium chloride solution with a concentration of 0.6 mol / L. Use a needle to draw 8 μL of the protein sample dilution and then immerse it in soybean oil. Detect the interfacial tension based on the change in the outer contour of the droplet.
[0131] 1-3. Determination of emulsion zeta potential and particle size: The emulsion was diluted 100 times with a sodium chloride solution with a concentration of 0.6 mol / L, and the zeta potential of the myofibrillar protein-based emulsion was measured using a Malvern Zetasizer Nano ZS analyzer. The emulsion droplet size was measured using a Malvern Mastersizer 3000E analyzer. Specifically, the emulsion sample (5 mL) was dispersed in distilled water with a refractive index of 1.330 to obtain an average particle size D4,3 value.
[0132] 1-4. Determination by confocal laser scanning microscopy (CLSM): The microstructure of the emulsion was observed using an OLYMPUS laser scanning microscope (model FY3000). 1 mL of myofibrillar protein-based emulsion was stained with 40 μL of Nile red ethanol solution (concentration of 0.1%, w / v) to mark the oil phase. After 5 minutes of dark reaction, the stained emulsion sample (10 μL) was placed on a microscope slide, covered with a coverslip, and a CLSM picture was taken with a 10x magnification eyepiece. Nile red fluorescent dye is excited at a wavelength of 488 nm.
[0133] 1-5. Take photos of emulsion: Take 15 mL of freshly prepared myofibrillar protein-based emulsion, place it in a glass bottle with an inner diameter of 20 mm and a height of 60 mm, and store it at room temperature. Take photos at 0, 30, and 60 minutes to observe the emulsion behavior.
[0134] 1-6. Multiple light scattering measurement: The turbiscan stability index (TSI) and backscattered light intensity (ΔBS) were measured using a Formulaaction stability analyzer (model Turbiscan TOWER) to evaluate the physical stability of the emulsion. 20 mL of freshly prepared myofibrillar protein-based emulsion was carefully placed in a measuring glass bottle and scanned from the bottom of the bottle upward every 120 seconds using a near-infrared light source with a wavelength of 880 nm for 60 minutes.
[0135] 1-7. Determination of microrheological properties: The microrheological properties of the emulsion were evaluated using a Rheolaser Master microrheometer. 20 mL of freshly prepared myofibrillar protein-based emulsion was placed in a measuring bottle and monitored for 1 h. RheosoftMaster 1.4.0.0 software was used to calculate characteristic parameters such as macro viscosity index (MVI), fluidity index (FI), and elasticity index (EI).
[0136] 2. Experimental results:
[0137] (1) The three-phase contact angle results obtained by the embodiments and comparative examples are as follows Figure 1As shown. The contact angle reflects the hydrophilicity of protein particles, which in turn affects their adsorption at the oil-water interface. For proteins, within 90°, the larger the contact angle, the more exposed hydrophobic groups. Compared with the blank control group (Comparative Example 1), the contact angle of the oxidized control group (Comparative Example 2) increased (p < 0.05), indicating that oxidation promoted the moderate unfolding of the myofibrillar protein structure and the exposure of hydrophobic groups. The contact angle of the polyphenol-damaged group (Comparative Example 3) was the largest, at 77.78 ± 0.36°. This is because the covalent and non-covalent modification of gallic acid accelerates the exposure of protein hydrophobic residues and reduces the hydrophilicity of the protein. In this case, the over-exposed hydrophobic groups will induce myofibrillar protein aggregation under the action of strong hydrophobic forces, hindering the diffusion of proteins at the oil-water interface and deteriorating the emulsification performance. After encapsulating gallic acid with the zein / polysaccharide nanosystem, the contact angle of myofibrillar protein particles was significantly lower than that of the polyphenol-damaged group (p < 0.05). The contact angle of the myofibrillar protein particles with improved emulsification properties obtained in Example 1 was 63.35±0.08°, which was 19% lower than that of the polyphenol-damaged group; the contact angle of the myofibrillar protein particles with improved emulsification properties obtained in Example 2 was 64.72±0.13°, which was 17% lower than that of the polyphenol-damaged group; the contact angle of the myofibrillar protein particles with improved emulsification properties obtained in Example 3 was 65.78±0.15°, which was 15% lower than that of the polyphenol-damaged group. The use of the zein / polysaccharide nanosystem to encapsulate gallic acid weakened the interaction between gallic acid and myofibrillar protein and reduced the aggregation level of the protein.
[0138] (2) The interfacial tension results obtained by the embodiments and comparative examples are as follows Figure 2 As shown. The polyphenol-damaged group (Comparative Example 3) exhibited the highest interfacial tension. This is because high doses of gallic acid induced myofibrillar protein to form large insoluble aggregates, burying some of the exposed hydrophobic groups and reducing the binding of protein to oil droplets. In addition, the formation of aggregates also hindered the migration and diffusion of protein to the oil-water interface. Compared with the polyphenol-damaged group, the interfacial tension of myofibrillar protein with improved emulsification properties obtained in the example was significantly decreased. Encapsulating gallic acid in zein / polysaccharide nanoparticles limits the interaction between gallic acid and myofibrillar protein under oxidative stress, inhibits the formation of protein aggregates, improves the flexibility and surface activity of the protein conformation, and thus promotes the interfacial adsorption of myofibrillar protein.
[0139] (3) The emulsion potential results obtained by the embodiments and comparative examples are as follows Figure 3As shown. All emulsion samples are electronegative. Compared with the blank control group (Comparative Example 1), the absolute value of the zeta potential of the oxidized control group (Comparative Example 2) increased significantly (p < 0.05), which is related to the exposure of negatively charged groups. The absolute value of the zeta potential of the polyphenol-damaged group (Comparative Example 3) is the smallest, which is 27.03 ± 0.37 mV. This is because the interaction between gallic acid and myofibrillar protein induces protein cross-linking aggregation, thereby reburying the exposed negatively charged amino acid residues. This reduces the electrostatic repulsion between the emulsion droplets, resulting in poor emulsion stability. After encapsulating gallic acid with zein / polysaccharide nanosystem, the absolute value of the zeta potential of the myofibrillar protein-based emulsion was significantly higher than that of the polyphenol-damaged group (p < 0.05), and the absolute values were all greater than 30 mV, indicating that the stability of the emulsion was improved. The absolute value of the zeta potential of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 1 was 38.49±0.89mV, which was 42% higher than that of the polyphenol-damaged group; the absolute value of the zeta potential of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 2 was 35.34±0.78mV, which was 31% higher than that of the polyphenol-damaged group; the absolute value of the zeta potential of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 3 was 34.60±0.93mV, which was 28% higher than that of the polyphenol-damaged group. The use of the zein / polysaccharide nanosystem to encapsulate gallic acid reduces the aggregation of myofibrillar protein, allowing more negatively charged proteins to be adsorbed on the oil-water interface, increasing the electronegativity of the droplets. In addition, due to the good amphiphilicity of zein, zein / polysaccharide nanoparticles loaded with gallic acid may also be involved in the formation of the interfacial film; the presence of anionic polysaccharides can increase the negative charge of the interfacial protein and improve the stability of the emulsion by increasing the electrostatic repulsion and the viscosity of the continuous phase.
[0140] (4) The results of the emulsion particle size distribution and average particle size obtained by the embodiment and the comparative example are as follows: Figure 4 and Figure 5 All emulsion samples showed a bimodal distribution with a main peak (10-100 μm) and a weak peak (100-1000 μm). Compared with the blank control group (Comparative Example 1), the average particle size D 4,3 The value was significantly increased (p<0.05). 4,3 The maximum value is 86.5±0.5μm. This is because high doses of gallic acid induce excessive aggregation of myofibrillar protein, which cannot generate sufficient interfacial pressure to maintain the dispersion of emulsion droplets, thereby reducing the stability of the emulsion. After encapsulating gallic acid with zein / polysaccharide nanosystem, the D 4,3The value was significantly lower than that of the polyphenol injury group (p<0.05). 4,3 The value was 50.4±0.1μm, which was 42% lower than that of the polyphenol-damaged group; the D 4,3 The value was 54.0±0.0μm, which was 38% lower than that of the polyphenol-damaged group; the D 4,3 The value was 59.7±1.1μm, which was 31% lower than that of the polyphenol injury group. The use of zein / polysaccharide nanosystem to encapsulate gallic acid promoted the release of some myofibrillar proteins from insoluble aggregates induced by high-dose gallic acid, which gave the protein a larger adsorption area and higher interfacial activity at the oil-water interface, thereby preventing the aggregation of oil droplets. In addition, the high viscosity of polysaccharides in the continuous phase also restricted the movement of oil droplets, preventing them from merging into large aggregates, thereby improving the stability of the emulsion.
[0141] (5) The results of the emulsion microstructures obtained by the embodiments and comparative examples are as follows Figure 6 As shown. Compared with the blank control group (Comparative Example 1) and the oxidized control group (Comparative Example 2), oil droplet aggregation was observed in the polyphenol-damaged group (Comparative Example 3), and the oil droplets became larger and uneven, indicating that the internal structure of the emulsion was destroyed. Compared with the polyphenol-damaged group, the droplet size of the myofibrillar protein-based emulsion with improved emulsification properties obtained in the embodiment became smaller and more evenly distributed. Encapsulating gallic acid in zein / polysaccharide nanoparticles prevents excessive interaction between gallic acid and myofibrillar protein, which is conducive to the adsorption of more proteins on the surface of oil droplets and the formation of a uniform and dense interfacial film, thereby enhancing the stability of the emulsion. The high electrostatic repulsion and steric resistance caused by the presence of polysaccharides also help to overcome the aggregation of emulsion droplets. This is consistent with the results of zeta potential and emulsion particle size.
[0142] (6) The results of the emulsion emulsion behavior obtained by photographing the examples and comparative examples are as follows Figure 7 As shown. The blank control group (Comparative Example 1) and the oxidation control group (Comparative Example 2) did not stratify after storage at room temperature for 60 minutes and were stable. However, the polyphenol-damaged group (Comparative Example 3) showed obvious phase separation, and the emulsion layer gradually moved upward, indicating that the addition of high-dose gallic acid made the myofibrillar protein-based emulsion unstable. Compared with the polyphenol-damaged group, the myofibrillar protein-based emulsion with improved emulsification properties obtained in the example had a lower degree of phase separation and improved stability of the emulsion.
[0143] (7) The results of the emulsion TSI measured in the examples and comparative examples are as follows Figure 8As shown. The lower the TSI value, the more stable the emulsion. The TSI value of the polyphenol-damaged group (Comparative Example 3) is the highest, indicating that the emulsion is in an unstable state. Compared with the polyphenol-damaged group, the TSI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in the example is significantly reduced, indicating that the stability of the emulsion is significantly improved. The results of the emulsion ΔBS measured in the examples and comparative examples are shown in Fig. 9 As shown. Generally speaking, a decrease in the ΔBS value is shown as a negative peak, which appears on the left side of the horizontal axis, indicating that clarification occurs at the bottom of the bottle; the positive peak on the right side of the horizontal axis (i.e., an increase in the ΔBS value) indicates that a creaming layer appears at the top of the bottle. The ΔBS change in the polyphenol-damaged group (Comparative Example 3) was the most obvious, and the height of the clear liquid at the bottom of the emulsion reached 15 mm. This shows that the addition of high doses of gallic acid causes the oil droplets in the emulsion to move upward, flocculation / agglomeration occurs at the top, and the stability of the emulsion is destroyed. After encapsulating gallic acid using the zein / polysaccharide nanosystem, the height of the clear liquid at the bottom of the myofibrillar protein-based emulsion decreased significantly. The height of the clear liquid at the bottom of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 1 was 1.48 mm, which was 90% lower than that of the polyphenol-damaged group; the height of the clear liquid at the bottom of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 2 was 1.80 mm, which was 88% lower than that of the polyphenol-damaged group; the height of the clear liquid at the bottom of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 3 was 1.92 mm, which was 87% lower than that of the polyphenol-damaged group. Encapsulating gallic acid in zein / polysaccharide nanoparticles inhibited the formation of myofibrillar protein aggregates induced by high doses of gallic acid, thereby improving the stability of the emulsion; at the same time, the presence of anionic polysaccharides increased the viscosity of the continuous phase and the electrostatic repulsion of the emulsion system, further preventing the migration and aggregation of oil droplets. The results of the emulsion microstructure well support this point.
[0144] (8) The results of the microrheological properties of the emulsions measured in the examples and comparative examples are as follows Fig.10 shown. Fig.10 A, B, and C correspond to the changes in MVI, FI, and EI values, respectively. The higher the MVI value, the slower the particle movement speed and the higher the macroscopic viscosity of the emulsion. The MVI value of the polyphenol damage group (Comparative Example 3) was the lowest, and the final MVI value was 2.24×10 -4 nm -2 ·s. Compared with the polyphenol-damaged group, the MVI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 1 increased significantly, indicating that the macroscopic viscosity of the emulsion increased. The final MVI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 1 was 3.3×10 -3 nm -2 ·s, which was 13.7 times higher than that of the polyphenol-damaged group: The final MVI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 2 was 1.45×10 -3 nm-2 ·s, which was 5.5 times higher than that of the polyphenol-damaged group; the final MVI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 3 was 7.53×10 -4 nm -2 ·s, which was 2.4 times higher than that of the polyphenol-damaged group. The use of zein / polysaccharide nanosystem to encapsulate gallic acid hindered the excessive interaction between gallic acid and myofibrillar proteins, which was beneficial to promote the normal cross-linking between proteins, thereby providing a higher flow barrier; in addition, the presence of anionic polysaccharides further increased the flow resistance, interfered with the Brownian motion and diffusion of droplets, reduced the chance of droplets colliding with each other, and hindered the aggregation of droplets.
[0145] The FI value reflects the fluidity of the emulsion droplets and is negatively correlated with the MVI value. Fig.10 As shown in B, the FI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example 1 is lower than that of the polyphenol-damaged group, indicating that the emulsion stability is improved. The EI value is positively correlated with the elasticity of the sample. Fig.10 As shown in Figure C, the EI value of the myofibrillar protein-based emulsion with improved emulsification properties obtained in Example is much higher than that of the polyphenol-damaged group, indicating that the interaction between the emulsion droplets is enhanced and the elasticity of the emulsion is increased. In summary, the microrheological results show that the encapsulation of gallic acid and the presence of polysaccharides increase the viscosity of the myofibrillar protein-based emulsion, reduce its fluidity, and delay the collision and migration of droplets due to Brownian motion and diffusion, thereby making the emulsion have a smaller droplet size and good physical stability.
[0146]
Average particle size and zeta potential determination of gallic acid-zein / polysaccharide nanocomposites
[0147] 1. Experimental method: The gallic acid-zein / polysaccharide nanocomposite powder obtained in step 25 was dissolved in deionized water (pH 4.0) to obtain a sample solution with a concentration of 0.5 mg / mL. The particle size and zeta potential of the sample solution were measured using a Malvern Zetasizer Nano ZS analyzer.
[0148] 2. Experimental results: The particle size determination results of gallic acid-zein / polysaccharide nanocomplexes are as follows: Fig.11 The average particle sizes of the gallic acid-zein / sodium alginate, gallic acid-zein / gum arabic, and gallic acid-zein / xanthan gum complexes were all below 550 nm, indicating that nanoparticles were formed. The zeta potential measurement results of the gallic acid-zein / polysaccharide nanocomposite are shown in Fig.12As shown in the figure. Due to the presence of anionic polysaccharides, the gallic acid-zein / polysaccharide nanocomposites are electronegative, and the zeta potentials are -45.60 mV (gallic acid-zein / sodium alginate), -29.11 mV (gallic acid-zein / gum arabic), and -35.35 mV (gallic acid-zein / xanthan gum).
[0149] [Determination of encapsulation efficiency and antioxidant activity of gallic acid and gallic acid-zein / polysaccharide nanocomplexes]
[0150] 1. Experimental methods:
[0151] 1-1. Determination of encapsulation efficiency: The supernatant obtained in step 25 is concentrated by rotary evaporation to remove water, and the residue is washed three times with anhydrous ethanol to remove free gallic acid. The three washing solutions are recovered and used to determine the content of free gallic acid. The method is as follows: 0.5 mL of the test solution is mixed with an equal volume of Folin-phenol reagent, allowed to stand for 6 minutes, and then 1 mL of 10% (w / v) sodium carbonate solution is added. After reacting for 1 hour, the absorbance of the mixed solution at a wavelength of 760 nm is determined by a Hitachi U-5100 spectrophotometer. A standard curve is drawn using gallic acid (concentration of 2-10 μg / mL) as the standard. The encapsulation efficiency is calculated according to formula (3):
[0152]
[0153] 1-2. Determination of antioxidant activity: Without removing free gallic acid, the DPPH free radical scavenging activity and ABTS free radical scavenging activity before and after gallic acid encapsulation were determined, and the half effective concentration (EC 50 ), as follows:
[0154] (1) DPPH radical scavenging rate: Take 0.5 mL of the sample to be tested (concentrations are 5, 10, 15, 20, 25 μg / mL) and mix thoroughly with 3 mL of DPPH ethanol solution (concentration is 0.1 mmol / L). Incubate in the dark for 30 min and measure the absorbance at a wavelength of 517 nm. Use ethanol instead of the sample as a control. The DPPH radical scavenging rate is calculated according to formula (4):
[0155]
[0156] (2) ABTS free radical scavenging rate: 10 mL of ABTS solution (concentration 7 mmol / L) was mixed with 176 μL of potassium persulfate solution (concentration 140 mmol / L) and reacted in the dark for 16 h. The mixture was diluted with deionized water to an absorbance value of A 734nmis 0.7 to obtain an ABTS free radical solution. Take 0.1 mL of the sample to be tested (concentrations are 10, 20, 30, 40, 50 μg / mL) and add it to 5 mL of the ABTS free radical solution. React in the dark for 6 minutes and measure the absorbance at a wavelength of 734 nm. Use deionized water instead of the sample as a control. The ABTS free radical scavenging rate is calculated according to formula (5):
[0157]
[0158] 2. Experimental results: Encapsulation efficiency and free radical scavenging activity EC 50 The results of the values are shown in Table 2. The encapsulation efficiencies of gallic acid-zein / sodium alginate, gallic acid-zein / gum arabic, and gallic acid-zein / xanthan gum nanocomposites were 67.50±0.65%, 60.74±0.40%, and 59.91±0.41%, respectively. The results indicate that the zein / polysaccharide nanosystem has a good encapsulation ability for gallic acid. In addition, there was no significant change in the antioxidant activity before and after gallic acid encapsulation (p>0.05). Considering the limited antioxidant capacity of zein and polysaccharides, the free radical scavenging activity of the gallic acid-zein / polysaccharide nanocomposites mainly comes from gallic acid. The results indicate that the gallic acid-zein / polysaccharide nanocomposites can still be used as strong antioxidants in meat processing to protect muscle protein from oxidative damage.
[0159] Table 2 Encapsulation efficiency and antioxidant activity of gallic acid and gallic acid-zein / polysaccharide nanocomposites
[0160]
[0161] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, characterized in that: The following steps are involved: Step 1, extracting myofibrillar protein from chicken breast; Step 2, adding the myofibrillar protein obtained in step 1 to the gallic acid-zein / polysaccharide nanocomposite solution, and homogenizing with a homogenizer to obtain a myofibrillar protein suspension; Step 3, adding the Fenton oxidation system to the myofibrillar protein suspension obtained in step 2 to obtain a myofibrillar protein sample; reacting the myofibrillar protein sample in an environment of 0 to 4° C. for 10 to 14 hours to obtain a reacted myofibrillar protein sample; Step 4: Mix the myofibrillar protein sample obtained in step 3 with soybean oil, and homogenize with a homogenizer to obtain an oil-in-water emulsion, which is a myofibrillar protein-based emulsion with improved emulsification properties.
2. The method of claim 1 for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, characterized in that: In step 2, the gallic acid-zein / polysaccharide nanocomposite solution preparation process is as follows: Step 21, dissolving 15 to 30 mg of zein in 8 to 12 mL of an ethanol aqueous solution having a volume fraction of 80% to 95%, and stirring with a magnetic stirrer for 0.5 to 2 h to obtain a zein solution; Step 22, adding 2 mg of gallic acid to the zein solution obtained in step 21, stirring with a magnetic stirrer for 1.5 to 3 hours to obtain a gallic acid-zein mixture; then centrifuging the gallic acid-zein mixture at a speed of 2000 to 5000 g for 10 minutes using a centrifuge, and the obtained supernatant is the gallic acid-zein solution; Step 23, dissolving 30-45 mg of polysaccharide in 18-22 mL of deionized water, stirring with a magnetic stirrer for 0.5-2 h to obtain a polysaccharide aqueous solution; adjusting the pH value of the polysaccharide aqueous solution to 3.5-5.0 with a 1 mol / L hydrochloric acid solution to obtain a polysaccharide solution; Step 24, under magnetic stirring conditions, dropwise adding the gallic acid-zein solution obtained in step 22 into 8-12 mL of deionized water with a pH value of 3.5-5.0, and continuing to stir with a magnetic stirrer for 3-8 minutes to obtain a gallic acid-zein ethanol dispersion; removing ethanol from the gallic acid-zein ethanol dispersion by a rotary evaporator, and then adding deionized water with a pH value of 3.5-5.0 to supplement the total volume to 18-22 mL, to obtain a gallic acid-zein dispersion; Step 25. Under magnetic stirring conditions, add the gallic acid-zein dispersion obtained in step 24 to the polysaccharide solution obtained in step 23, and continue stirring with a magnetic stirrer for 3 to 8 minutes to obtain a gallic acid-zein / polysaccharide complex; centrifuge the gallic acid-zein / polysaccharide complex at a speed of 2000 to 5000 g for 10 minutes to obtain a supernatant, and then dry the supernatant with a freeze dryer to obtain a gallic acid-zein / polysaccharide nanocomposite powder. Step 26: dissolving the gallic acid-zein / polysaccharide nanocomposite powder obtained in step 25 in 14-18 mL of a 0.6 mol / L sodium chloride solution to obtain a gallic acid-zein / polysaccharide nanocomposite solution.
3. The method of claim 1 for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, characterized in that: In step 23, the polysaccharide is sodium alginate, gum arabic or xanthan gum.
4. The method of claim 1 for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, characterized in that: In step 3, the final concentration of myofibrillar protein in the myofibrillar protein sample is 4-8 mg / mL, the final concentration of ferric chloride in the Fenton oxidation system is 25-40 μmol / L, the final concentration of ascorbic acid is 275-350 μmol / L, and the final concentration of hydrogen peroxide is 8-12 mmol / L.
5. The method of claim 1 for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, characterized in that: In step 4, the volume ratio of the myofibrillar protein sample to the soybean oil is 3:1 to 5:
1.
6. The method of claim 1 for improving the damage of high-dose gallic acid to the emulsification properties of meat protein by using zein / polysaccharide nanosystem, characterized in that: In step 4, the speed of the homogenization process is 10000-13000 rpm, and the homogenization time is 1-3 min.